Targeting the insulin-like growth factor-1 receptor in human cancer - Arcaro, Alexandre (Frontiers in Pharmacology, 2013)
The insulin-like growth factor (IGF) signaling system plays a crucial role in human cancer and the IGF-1 receptor (IGF-1R) is an attractive drug target against which a variety of novel anti-tumor agents are being developed. Deregulation of the IGF signaling pathway frequently occurs in human cancer and involves the establishment of autocrine loops comprising IGF-1 or -2 and/or IGF-1R over-expression. Epidemiologic studies have documented a link between elevated IGF levels and the development of solid tumors, such as breast, colon and prostate cancer. Anticancer strategies targeting the IGF signaling system involve two main approaches, namely neutralizing antibodies and small molecule inhibitors of the IGF-1R kinase activity. There are numerous reports describing anti-tumor activity of these agents in pre-clinical models of major human cancers. In addition, multiple clinical trials have started to evaluate the safety and efficacy of selected IGF-1R inhibitors, in combination with standard chemotherapeutic regimens or other targeted agents in cancer patients. In this Mini Review, I will discuss the role of the IGF signaling system in human cancer and the main strategies which have been so far evaluated to target the IGF-1R.